Ocean warming expands habitat of a rich natural resource and benefits a national economy. Issue 7 (12th September 2016) - Jansen, Teunis; Post, Søren; Kristiansen, Trond; Óskarsson, Guðmundur J.; Boje, Jesper; MacKenzie, Brian R.; Broberg, Mala; Siegstad, Helle
Abstract: Geographic redistribution of living natural resources changes access and thereby harvesting opportunities between countries. Internationally shared fish resources can be sensitive to shifts in the marine environment and this may have great impact on the economies of countries and regions that rely most heavily on fisheries to provide employment and food supply. Here we present a climate change‐related biotic expansion of a rich natural resource with substantial economic consequences, namely the appearance of northeast Atlantic mackerel ( Scomber scombrus ) in Greenlandic waters. In recent years, the summer temperature has reached record highs in the Irminger Current, and this development has expanded the available and realized mackerel habitat in time and space. Observations in the Irminger Current in east Greenland in 2011 of this temperature‐sensitive epipelagic fish were the first records so far northwest in the Atlantic. This change in migration pattern was followed by a rapid development of a large‐scale fishery of substantial importance for the national economy of Greenland (23% of Greenland's export value of all goods in 2014). A pelagic trawl survey was conducted in mid‐summer 2014 and the results showed that the bulk of 1 million Mg (=t) of mackerel in the Irminger Current in southeast Greenland were located in the relatively warm (>8.5°C) surface layer. Mackerel was also observed in southwest Greenland. Finally, 15 CMIP5 Earth System Model projections of future marine climate were used to evaluate the epipelagic environment in Greenland. These projections for moderate and high CO2 emission scenarios (representative concentration pathways [RCP] 4.5 and 8.5) suggest how the available mackerel habitat may expand further in space and time. Overall, our results indicate that, if the stock remains large, productive, and continues its current migration pattern, then climate change has provided Greenland with a new unique opportunity for commercial exploitation. However, positive cases like this should not be cherry‐picked and misused as arguments against timely and effective mitigation of climate change.